Effect of β-spodumene additions on the phase composition, thermal, mechanical, and fracture behavior of zirconia toughened alumina composites - S.M. Naga; M. Sayed; Khaled A. Omran; M.A.H. El-Meniawi; Hossam El-Din M. Sallam; O. Hanzel; A.M. Hassan (Journal of Materials Research and Technology, 2024)
The fabrication of ceramic composites with low thermal expansion and excellent mechanical properties is essential for thermal barrier coating (TBC) applications. For this purpose, using the sol-gel process, novel ceramic composites were developed by combining varying weight percentages of β-spodumene (0–20 wt%) with zirconia toughened alumina (ZTA). The influence of β-spodumene addition on the densification, phase composition, microstructure, and mechanical, thermal, and fracture behavior of the studied composites was investigated experimentally and numerically. Increasing the β-spodumene content reduces the sintering temperature of the formed composites by 75 °C. Introducing 5 wt% β-spodumene to ZTA composite improves the densification process by serving as a mineralizer. X-ray diffraction (XRD) revealed that the t-m ZrO2 transformation was enhanced by increasing the β-spodumene content. The results demonstrated that composites with β-spodumene content of 5 wt% exhibited the best mechanical performance. The numerical prediction of fracture toughness agreed well with the experimental results for different composites.